Epithelial-mesenchymal interactions in the developing kidney lead to expression of tenascin in the mesenchyme (The Rockefeller University Press, 1987)
Tenascin, a mesenchymal extracellular matrix glycoprotein, has been implicated in epithelial-mesenchymal interactions during fetal development (Chiquet-Ehrismann, R., E. J. Mackie, C. A. Pearson, T. Sakakura, 1986, Cell, 47:131-139). We have now investigated the expression of tenascin during embryonic development of the mouse kidney. In this system, mesenchymal cells convert into epithelial cells as a result of a tissue interaction. By immunofluorescence, tenascin could not be found in the mesenchyme until kidney tubule epithelial began to form. It then became detectable around condensates and s- shaped bodies, the early stages of tubulogenesis. In an in vitro culture system, tenascin expression by the mesenchyme is tightly coupled to the de novo formation of epithelial, and does not occur if tubulogenesis is suppressed. The results strongly suggest that the formation of the new epithelium stimulates the expression of tenascin in the nearby mesenchyme. During postnatal development, the expression of tenascin decreases and the spatial distribution changes. In kidneys from adult mice, no tenascin can be found in the cortex, but interspersed patches of staining are visible in the medullary stroma. The results strongly support the view that tenascin is involved in epithelial-mesenchymal interactions. It could therefore be crucial for embryonic development.